Kelembagaan Pertanian di Desa Cibanteng: Strategi Pengembangan dan Tantangan - Fachrunnisa, Siti Rhaina; Ardiawati, Fadilla; Hafizh, Rahmat Nur; Wardiani, Shafira Rizky; Lestari, Veryna Widia (Jurnal Sains Sosio Humaniora, 2025)
Agricultural institutions have a strategic role in supporting sustainable agricultural development and improving farmer welfare. This research aims to analyze strategies for strengthening agricultural institutions to make them more responsive and adaptive to the needs of local communities, identify challenges in accessing technological innovation and market-oriented training, and provide practical recommendations for increasing the productivity and competitiveness of farmers in Cibanteng Village. With a qualitative approach, data was obtained through in-depth interviews, participant observation and document analysis. The research results show that agricultural institutions in Cibanteng Village face various challenges, including low access to training and technology and weak coordination between farmers and external parties. To overcome this, a strategy is needed that includes market needs-based training, strengthening cooperation networks, and agricultural technology innovation. This research recommendation emphasizes the importance of cross-sector support in developing adaptive and